The dark sides of low-carbon innovations for net-zero transitions: a literature review and priorities for future research - Sophie-Marie Ertelt; Per Carlborg (Sustainability: Science, Practice, & Policy)
The rapid commercialization, diffusion, and adoption of low-carbon innovation will have a pivotal role to play on the path to net-zero emissions globally. Therefore, in the context of climate-change mitigation and decarbonization, it is no surprise that we can observe an inherently optimistic view on the prospects of low-carbon innovation among scholars, specifically in the research domains of innovation management and sustainability transitions. Yet, simply taking for granted that innovation-led decarbonization processes universally will produce beneficial outcomes for society runs the risk of neglecting potential adverse effects or negative consequences that might accompany the deployment of these technologies. Therefore, knowledge of the dark sides of low-carbon innovation is crucial for developing policies and innovation-management strategies that enable truly economically, environmentally, and socially sustainable net-zero transitions. Through a systemic literature review, this study systematizes the extant research on the topic and proposes a typology of negative consequences of low-carbon innovations: (1) Jevons Paradox, (2) social consequences and cultural barriers, (3) economic consequences, and (4) environmental consequences and problem-shifting effects. Based on these categories, we put forward a research agenda with key priorities for future research.